Re-evaluating patient isolation policies for musculoskeletal infections in orthopaedic practice: a scoping review - Sigmund, Irene K; Schuermans, Annette; Chen, Baixing; Wouthuyzen-Bakker, Marjan; Metsemakers, Willem-Jan; Soriano, Alex; Sousa, Ricardo; Bessems, Laura; Onsea, Jolien; Ferry, Tristan; Clauss, Martin; Kuehl, Richard (Journal of bone and joint infection, 2025)
Introduction: Historically, isolating patients diagnosed with musculoskeletal infections (MSIs) from the general orthopaedic population has been regarded a fundamental aspect of effective infection control. However, this remains controversial. Evolving perspectives on infection prevention, resource constraints, and staffing shortages necessitate a reassessment of current practices. This scoping review examines existing isolation policies for MSIs in orthopaedic practice and provides expert recommendations for hospital policymakers. Materials and methods: A systematic search of seven databases identified 23 320 articles. After deduplication and screening of 10 621 abstracts, 119 full texts were reviewed and 14 studies met the inclusion criteria. A total of 9 studies involved surgical wards, 5 examined general hospital wards, and 2 addressed orthopaedic patients. Results: Evidence indicates that individual isolation measures can reduce methicillin-resistant Staphylococcus aureus infections, whereas additional contact precautions or isolation showed no reduction of transmission risk for extended-spectrum beta-lactamase-producing Enterobacterales in endemic settings. For vancomycin-resistant Enterococcus (VRE), one study found a reduction in infections after implementing individual isolation, while another study reported no impact. No evidence supports separating patients with non-resistant MSIs from elective orthopaedic patients. Similarly, no data support the routine use of dedicated septic wards in orthopaedic practice. Conclusions: Effective infection control relies on hospital-wide strategies, provided that appropriate preventive measures and a high level of compliance with standard precautions are in place. Isolation practices should be selectively tailored to local epidemiology to balance infection prevention with optimal resource utilization. Managing MSIs in specialized centres, instead of dedicated septic wards, may deliver more effective care and adherence to standard precautions.